Financial dynamics of energy companies during global economic crisis. (17th June 2019) - Iovino, Felicetta; Migliaccio, Guido
This paper aims to analyse financial structure of energy companies, in the period during the crisis in relation to two discriminating factors. At this end, the research questions are: what is the actual situation and what the trend has been in the last eight years in the various Italian geographic areas and business markets; if there are differences between business markets and geographic area and if these differences are statistically significant. The trend analysis and analysis of variance (ANOVA) have been used starting from secondary data on AIDA database (at the end 428 energy suppliers). The financial structure is assessed using two ratios: the financial leverage ratio and quick ratio. The findings show that the financial structure of energy suppliers have not been substantially affected by the crisis in any geographic area and business market. Moreover, these two factors produce statistically significant differences in the financial structure of energy companies.